Investment Literacy and Family Financial Planning Program - Muslim Muslim (Advances in Community Services Research, 2026)
Purpose: This study systematically examines the roles of financial literacy and investment literacy in strengthening family financial planning, particularly their contribution to sustainable household financial management. Research Method: A qualitative Systematic Literature Review (SLR) was conducted on academic articles published between 2018 and 2025 in high-impact journals from Elsevier, Emerald, Wiley, and Springer. The selected studies were systematically identified, screened, and analyzed using thematic analysis to synthesize recurring patterns and key findings. Results and Discussion: Six major themes emerged: basic financial literacy as the foundation of family financial planning; integration of investment literacy into household decision-making; family financial socialization; demographic influences on financial decisions; sociocultural dynamics in financial strategies; and the effectiveness of family-based literacy programs. These findings support the Theory of Planned Behavior and the family financial socialization perspective. Implications: Policymakers, educators, and communities should develop contextual, participatory, and sustainable family financial literacy programs. Future research should empirically examine the interaction between financial and investment literacy across diverse family contexts. Originality: This study integrates financial literacy, investment literacy, and family financial socialization into a unified framework for understanding sustainable family financial planning.